The genome sequence of the Pinion-spotted Pug, Eupithecia insigniata (Hübner, 1790) - Holland, PWH (F1000Research, 2023)
We present a genome assembly from an individual male Eupithecia insigniata (the Pinion-spotted Pug; Arthropoda; Insecta; Lepidoptera; Geometridae). The genome sequence is 438.1 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.52 kilobases in length.